Crapanzano's Literature : Antidote to Temporal Relegation of the Navajo (Canadian Journal of Native Studies, 2026)
The American anthropologist Vincent Crapanzano eulogizes theNavajo and Apache in his work Imaginary Horizons: An Essay inLiterary-Philosophical Anthropology in order to linguistically capturethe essence of Self and Other, in the spirit of mutual celebration.The difficult path to striking the delicate balance necessaryto speak about the other when he is not always part of theconversation is delivered in this article by looking at figures ofspeech that are used to connect the interlocutors, but which havein-built distancing power that unfortunately involuntarily temporallyrelegates the native (excludes him because his physicalabsence signifies that he exists in a not-so-distant past in comparisonto the interlocutor telling the story, in the present). Thisis evident in the poetic appropriation of the myth of the noblesavage as well as the hinterland metaphor, which are used fordescribing native characters and their geographical origin. Thispiece discusses the difficulty to speak about aboriginal subjectsby non-aboriginal researchers. It is shown that imagination isthe work that reconnects, and poetry the work that gives voice.